Cerebral Tissue Regional Oxygen Saturation as a Valuable Monitoring Parameter in Pediatric Patients Undergoing Extracorporeal Membrane Oxygenation - Chen, Song; Fang, Fang; Liu, Wenjun; Liu, Chengjun; Xu, Feng (Frontiers in Pediatrics, 2021)
Objective: Brain function monitoring technology for extracorporeal membrane oxygenation (ECMO) support has been developing quite slowly. Our objective was to explore the data distribution, variation trend, and variability of cerebral tissue regional oxygen saturation (CrSO2) in pediatric patients undergoing ECMO. Methods: Eight patients who received venoarterial ECMO (V-A ECMO) were included in our study. All of them accepted continuous CrSO2 monitoring by near-infrared spectroscopy (NIRS) within 12 h of ECMO initiation until ECMO wean. Differences in the CrSO2 distribution characteristic, the variation trend of daily CrSO2, and the variability of CrSO2 for the first 5 days following ECMO initiation were compared between survivors and non-survivors according to pediatric intensive care unit (PICU) mortality. Results: The percentage of time of CrSO2 <60% against the whole monitoring time was significantly lower in survivors in both hemispheres {right: 4.34% [interquartile range (IQR) = 0.39–8.55%] vs. 47.45% [IQR = 36.03–64.52%], p = 0.036; left: 0.40% [IQR = 0.01–1.15%] vs. 30.9% [IQR = 26.92–49.62%], p = 0.036}. Survivors had significantly higher CrSO2 on the first 4 days. Root mean of successive squared differences (RMSSD), the variability variable of CrSO2, was significantly lower in survivors (right: 3.29 ± 0.79 vs. 6.16 ± 0.67, p = 0.002; left: 3.56 ± 1.20 vs. 6.04 ± 1.44, p = 0.039). Conclusion: Lower CrSO2, CrSO2 <60% over a longer period of time, and higher fluctuation of CrSO2 are likely associated with PICU mortality in pediatric patients undergoing V-A ECMO. Clinical Trial Registry: URL: http://www.chictr.org.cn/showproj.aspx?proj=46639, trial registry number: ChiCTR1900028021.